2010
DOI: 10.2522/ptj.20100123
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a Clinical Prediction Rule to Identify Patients With Neck Pain Likely to Benefit From Thoracic Spine Thrust Manipulation and a General Cervical Range of Motion Exercise: Multi-Center Randomized Clinical Trial

Abstract: The results of the current study did not support the validity of the previously developed CPR. However, the results demonstrated that patients with mechanical neck pain who received thoracic spine manipulation and exercise exhibited significantly greater improvements in disability at both the short- and long-term follow-up periods and in pain at the 1-week follow-up compared with patients who received exercise only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 32 publications
2
127
0
4
Order By: Relevance
“…2 RCTs [40,47], with different qualities ranging from fair to high, used either exercise or exercise plus thoracic manipulation to investigate effectiveness of thoracic manipulation on patients with mechanical neck pain. Recent evidence supports using exercise for alleviating pain and improving dysfunction and disability [1,27,40,47].…”
Section: Thoracic Manipulation Versus Exercisementioning
confidence: 99%
“…2 RCTs [40,47], with different qualities ranging from fair to high, used either exercise or exercise plus thoracic manipulation to investigate effectiveness of thoracic manipulation on patients with mechanical neck pain. Recent evidence supports using exercise for alleviating pain and improving dysfunction and disability [1,27,40,47].…”
Section: Thoracic Manipulation Versus Exercisementioning
confidence: 99%
“…In a study by Cleland et al 16) , one group was submitted to an exercise program and thoracic manipulation, and another group was submitted to the exercise program alone in five sessions over the course of four weeks. The group submitted to both manipulation and exercise demonstrated greater improvements in disability (initial NDI = 30 NDI in Week 1 = 16 NDI in Week 4 = 10 and NDI after six months = 8) than the group submitted to exercise alone (initial NDI = 29 NDI in Week 1 = 18 NDI in Week 4 = 15 and NDI after six months = 13).…”
Section: Discussionmentioning
confidence: 99%
“…Cleland et al 16) reported that an intervention often used by physiotherapists in the treatment of neck pain is the manipulation of the thoracic spine. In their study, thoracic manipulative treatment was performed in association with exercise in 140 patients, who were then evaluated by NDI at 1 week, 4 weeks and 6 months after treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Certain factors are known to be prognostic for the course of neck pain, and several interventions, including those provided by physical therapists, are likely to produce a favorable outcome. [5][6][7][8][9] Approximately 35% of persons with neck pain reported being seen by a physical therapist, the most frequently visited provider, 10 and evidence suggests that physical therapy can be an effective secondary prevention strategy for neck pain. 11 In recent years, organized efforts have been made to improve clinical outcomes and standardize physical therapy treatment, including using classification system approaches.…”
mentioning
confidence: 99%